Two new species of the genus Taphioporus Moseyko & Kirejtshuk (Chrysomelidae: Eumolpinae) from Baltic amber - Bukejs, Andris; Moseyko, Alexey G. (Zootaxa, 2015)
Two new species of Taphioporus Moseyko & Kirejtshuk are described and illustrated from Baltic amber: T. rufous sp. nov. and T. carsteni sp. nov. Members of this fossil genus are known from Baltic and Rovno amber. A key to species of Taphioporus is provided.